Nurses’ challenges and successes in caring for Syrian refugees - Bircan Kara; Sercan Kara (Medicine, 2026)
Türkiye hosts the world’s largest Syrian refugee population. This places major demands on healthcare staff. Nurses in border areas such as Hatay face specific challenges. They must provide care that respects cultural differences. This study explored the lived experiences of Turkish nurses caring for Syrian refugees. It focused on care challenges and successful adaptation strategies. This qualitative phenomenological study used Colaizzi’s 7-step method. It included 16 nurses in Hatay, Türkiye. All participants provided direct care to Syrian refugees. Data were collected through face-to-face, semi-structured interviews. Each interview lasted 30 to 40 minutes. Trustworthiness was supported by member checking, peer debriefing, and an audit trail. Four main themes emerged from the analysis. The first theme covered challenges in working with refugees. Nurses described different health beliefs and language barriers. These barriers made it difficult to obtain accurate health histories. The second theme concerned difficulty in understanding health needs. It included gender-sensitive care, signs of trauma, and symptoms lost in translation. The third theme covered barriers to healthcare access. These included fear of procedures, long registration steps, and a lack of trained interpreters. The fourth theme focused on support and successful strategies. Nurses used mobile translation applications, help from coworkers, professional networks, and emotional regulation strategies. These methods offered immediate help, but sustainable support systems were limited. Nurses caring for Syrian refugees showed resilience and developed informal coping strategies. However, institutional support remained limited. Training programs should be revised. Staff also need reliable human and digital resources. These resources may reduce cultural and language barriers in refugee care.